Bank operational training to improve the competence of teachers of Islamic banking expertise - Aidha Trisanty; Nur Feriyanto; Diana Wijayanti; Dityawarman El Aiyubbi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
The development of sharia banking in Indonesia makes the need for competent human resources continues to increase. It is an opportunity for vocational high schools (SMK) to produce graduates with sharia banking competencies, such as SMK Muhammadiyah Dukun in Magelang. However, the relatively new sharia banking department is one of the obstacles to producing competent graduates. SMK has problems in the competence of teachers and learning facilities. This service carries out several activities to deal with these problems, organizing basic training in sharia banking, carrying out practical field activities (in collaboration with practitioners and the sharia finance industry), internships in sharia financial institutions, create modules for teaching materials for the teaching and learning process) and assist in solving competency test case questions. The output of this activity is the availability of modules and certified teachers by the National Professional Certification Agency (BNSP), which are indicators of mastery of related competencies.